Edifikasi atau Konfusi? Analisis Kritis terhadap Penggunaan Bahasa Lidah dalam Ibadah Jemaat Berdasarkan 1 Korintus 14:2-11 - Wennar; Simanjuntak, Ferry (Sekolah Tinggi Teologi Immanuel Sintang Kal-Bar, 2024)
This study analyzes the use of tongues in congregational worship based on the theological perspective of 1 Corinthians 14:2-11. The main focus of the study is to assess whether the use of tongues brings edification or creates confusion among the congregation. Through a qualitative approach with a hermeneutic analysis method, this study found that tongues are only effective in building the faith of the congregation if accompanied by an interpretation that can be understood by all church members. Without interpretation, tongues are more likely to be confusing, especially for those who are new to worship, so that it can disrupt the church's testimony. Paul emphasized the importance of order and edification in worship, so the modern church needs to pay attention to these principles in worship practices. This study recommends practical guidance and theological training for church leaders and congregations to use the gift of tongues appropriately and wisely. Further studies are needed to explore the use of tongues in various contemporary church traditions in order to enrich theological understanding of biblical worship practices.